Perbandingan Kinerja Hbase dan MongoDB Sebagai Backend IoT Data Storage - Niki Yuniar Wicaksono; Eko Sakti Pramukantoro; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
IoT (Internet Of Things) is currently evolving as evidenced with many studies that discuss the IoT. IoT consists of two main components of the Internet and interconnected Things, to collect data and information into data storage media that can be processed as needed. However, there are challenges in building IoT data storage media, like a large data volumes, diverse forms and data formats. In previous research has developed a Framework of IoT data storage media from the sensor node. The Framework uses NoSQL MongoDB as its data storage. In this study, proposed an IoT NoSQL Hbase data storage using the MongoDB Framework because it free scema and good writing speed in the performance testing of random writing tests. This study, tested Hbase and MongoDB by testing ability to storage data in data storage. The result of this test is Hbase and MongoDB is able to receive and insert text data and image data. While for testing the Framework of data storage media with Hbase using storage testing For testing the performance of MongoDB, better result test on runtime parameters of 33s, throughput of 1559 ops/s, 48% Usage CPU, 67% Memory Usage, and 4354kb Disk I/O. When testing images the results of differences in slightly different better of MongoDB on Runtime parameters 64s, throughput 90 ops/s, CPU Usage 46%, Memory Usage 84%, while when testing Hbase images superior in Disk I/O parameters of 109.462kb.